2014
DOI: 10.1073/pnas.1405154111
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon imaging of Zn 2+ dynamics in mossy fiber boutons of adult hippocampal slices

Abstract: Mossy fiber termini in the hippocampus accumulate Zn 2+ , which is released with glutamate from synaptic vesicles upon neural excitation. Understanding the spatiotemporal regulation of mobile Zn 2+ at the synaptic level is challenging owing to the difficulty of visualizing Zn 2+ at individual synapses. Here we describe the use of zinc-responsive fluorescent probes together with two-photon microscopy to image Zn 2+ dynamics mediated by NMDA receptor-dependent long-term potentiation induction at single mossy fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…This staining is similar to that obtained recently using probe 6-CO 2 H–ZAP4. 21 Vesicular zinc in the brain is loaded by the ZnT3 (Slc30A3) transporter and this gene has been successfully knocked out in transgenic mice. 22 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This staining is similar to that obtained recently using probe 6-CO 2 H–ZAP4. 21 Vesicular zinc in the brain is loaded by the ZnT3 (Slc30A3) transporter and this gene has been successfully knocked out in transgenic mice. 22 …”
Section: Resultsmentioning
confidence: 99%
“…Additionally, we co-stained hippocampal slices with SpiroZin2 and the membrane-permeable green fluorescent Zn 2+ sensor ZP1, which was used previously to image mobile zinc in mossy fiber boutons. 21 …”
Section: Resultsmentioning
confidence: 99%
“…Another possible contribution for the observed inhibition is the reduction of action potential-induced calcium influx into presynaptic terminals by DCG-IV, followed by the suppression of transmitter release. Previous observations indicate that mGlu receptor 2 activation can inhibit zinc relase [ 30 ] and N-type voltage-gated calcium channels [ 31 , 32 ], which mediate glutamate release. Down-regulation of these channels, which are involved in synaptic transmission at the mossy fiber-CA3 synapses in the hippocampus [ 33 ], may result in the suppression of calcium-dependent glutamate release.…”
Section: Discussionmentioning
confidence: 99%
“…fibers. It has been shown that zinc is released from these fibers into the extracellular medium when electrical stimuli are delivered (Li et al 2001a;Quinta-Ferreira et al 2004;Khan et al 2014;Vergnano et al 2014) and that it enters to postsynaptic neurons following intense electrical or chemical stimulation (Vogt et al 2000;Li et al 2001aLi et al , 2001bUeno et al 2002;Ketterman and Li 2008). The exposition of the slices to a high concentration of exogenous potassium causes an enhancement of the measured fluorescence signals, considered to be associated with postsynaptic zinc changes (Li et al 2001b;Ketterman and Li 2008).…”
Section: A B Cmentioning
confidence: 99%